Fable or philosophical claim? Thomas of Aquinas in Pico's Oratio - Almási, Zsolt (Verbum – Analecta Neolatina, 2004)
The present paper aims at reading a famous passage on the freedom of choice from Giovanni Pico della Mirandola's Oratio in the light that St. Thomas of Aquinas' De ente et essentia might cast upon it so as to make room for a fresh reading of the Oratio. This attempt is significant, because as far as the critical tradition is concerned the part of Pico's work is entrapped in two extreme views: the one claims that it is a serious philosophical statement, while the other refuting this view notes that it can only be a rhetorical introduction to the main theme of the Oratio. Showing the disadvantages of these views, and thus refuting them, I will propose a more accommodating position for the interpretation of the passage, which consists in reading it as a modification of Aquinas' logico-ontological scheme with the objective to show how moral philosophy may help one see the ethical aspect of his life in greater depth.